Light sources and composition of the culture medium in the in vitro establishment of chia (Salvia hispanica L.) (Research, Society and Development, 2020)
The goal of this work was to determine the effect of light sources, concentration of salts and growth regulators on in vitro germination of chia seeds. It was tested superficial cleaning with 70% ethanol submersion for different times before rinsing with 1% sodium hypochlorite for 20 minutes. The effect of the concentration of salts of the MS culture medium (0, 25, 50 and 100%) and the types of lamps (fluorescent or LED) on germination were also evaluated. Apical segments obtained from the best treatment in the in vitro germination stage were used to evaluate the regeneration in MS media supplemented with NAA (0, 0.5, 1.0 mg.L-1) and  TDZ (0, 2.5, 5.0 mg.L-1). The results showed that the submersion of seeds for 30 seconds in ethanol was the most efficient treatment. Seeds incubated in growth media containing half force of MS media under different light sources did not modified the percentage of germination compared to control, but affected the plantlets size and fresh matter. The effects of NAA and TDZ on morphogenesis under LED light, showed the importance of NAA on rhyzogenesis, while the TDZ induced the formation of adventitious stems. It was possible to establish the protocol for seed cleaning and to obtain plantlets under LED light, which can be routinely used in micropropagation of chia.